Mountain bike racing stimulates osteogenic bone signaling and ingesting carbohydrate-protein compared with carbohydrate-only prevents acute recovery bone resorption dominance - Oosthuyse, T.; Bosch, A. N.; Kariem, N.; Millen, A. M. (The Journal of Strength and Conditioning Research, 2021)
Mountain biking, unlike road cycling, includes vibrational accelerations but whether it stimulates osteogenic signaling remains unknown. Furthermore, exercise nutrition influences bone turnover, and the effect of ingesting protein during multiday racing was investigated. We measured plasma bone turnover markers, C-terminal telopeptide of type1-collagen (ß-CTX) and N-terminal propeptides of type1-procollagen (P1NP), and osteocyte mechanosensory signaling factor, sclerostin (SOST), corrected for plasma volume change, before (pre-day 1) and 20-60 minutes after (post-day 3) a multiday mountain bike race in 18 male cyclists randomly assigned to ingest carbohydrate-only (CHO-only) or carbohydrate-with-casein protein hydrolysate (CHO-PRO) during racing. Fourteen cyclists (n = 7 per group) completed the race, and data were analyzed with p < 0.05 accepted as significant. Plasma SOST decreased similarly in both groups (mean ± SD, CHO-only: 877 ± 451 to 628 ± 473 pg/ml, p = 0.004; CHO-PRO: 888 ± 411 to 650 ± 443 pg/ml, p = 0.003), suggesting that osteocytes sense mountain biking as mechanical loading. However, the bone formation marker, P1NP, remained unchanged in both groups, whereas the bone resorption marker, ß-CTX, increased in CHO-only (0.19 ± 0.034 to 0.31 ± 0.074 ng/ml, p = 0.0036) but remained unchanged in CHO-PRO (0.25 ± 0.079 to 0.26 ± 0.074 ng/ml, p = 0.95). Mountain bike racing does stimulate osteogenic bone signaling but bone formation is not increased acutely after multiday mountain biking; investigation for a delayed effect is warranted. The acute recovery increase in bone resorption with CHO-only is prevented by ingesting CHO-PRO during racing.